Regional effects of federal tax shocks - Bernd Hayo; Matthias Uhl (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper studies regional output asymmetries following U.S. federal tax shocks. We estimate a vector autoregressive model for each U.S. state, utilizing the exogenous tax shock series recently proposed by Romer and Romer (2010) and find considerable variations: estimated output multipliers lie between -0.2 in Utah and -3.3 in Hawaii. Statistically, the difference between state and national output effect is significant in about half the U.S. states. Analyzing the determinants of differences in the magnitude of regional tax multipliers suggests that industry composition of output and sociodemographic characteristics help explain the observed asymmetry across U.S. states in the transmission of federal tax policy.
Keywords: E32; E62; H20; R10; R11; 330; Fiscal Policy; Tax Policy; Narrative Approach; U.S. States; Regional Effects; Asymmetries in Fiscal Policy Transmission; Steuerpolitik; Schock; Regionale Inzidenz; Teilstaat; USA